Upgraders and Downgraders Strategies in SATGAS Covid-19 Talk Show - Purbo Kusumastuti; Djatmika; Miftah Nugroho (Britain International for Academic Research (BIAR-Publisher), 2022)
Studies on pragmatics which are focusing on the discussion of speech act have been highlighting the issue of how speech act strategies are analyzed based on the forms, classifications, and functions. As the use of speech act strategies is usually correlated to the politeness strategy, the analyses needs to be taken further to the internal modification, for example is the use of upgraders and downgraders to see how words build the politeness in a context differently based on the degree of politeness they carry as stated on Trosborg (1995). This paper used SATGAS COVID-19 Talkshow as the research object for the talkshow uses a lot of upgraders and downgraders strategies. Moreover, the talkshow is unique in its topic which is related to health in which such talkshows haven’t been quite addressed in speech act studies. As for that, this paper discussed types and functions of upgraders and downgraders used in the talkshow as well as what speech act classifications in which the upgraders and downgraders are embedded. This paper was analyzed using the contextual method which the results show the dominant speech acts contain upgraders and downgraders are assertive and directive; the dominant types of upgraders and downgraders are adverbial intensifiers and modals. Moreover, the results have shown that the two main purposes of the use of the strategy are to emphazise the importance of some informations and to follow the politeness culture which some of them are driven by the factor of of the speaker’s religion. The most important part of this research is that there are downgraders’ markers which are specially bound to Indonesian context, ‘Insya Alloh’ and the use of pronouns and upgraders’ marker ‘buanyak’. Nevertheless, this study only focusing on the talk show which only focusing on the health domain, moreover; the studies related to upgraders and downgraders in Indonesian context have not been quite addressed, next researchers could have more broaden scope of the study related to upgraders and downgraders, for example related to gender studies.